Developing a learning mix for the Open University Malaysia - Kaur, Abtar; Ansary Ahmed (Pfeiffer, 2004)
showcase a model of blended learning that is used by the recently established Open University Malaysia (OUM). In this model, learning experiences are offered through: (1) self-managed learning, (2) F2F learning, and (3) online (virtual classroom) learning. Self-managed learning (using print materials) is the most dominant element in the model, accounting for approximately 70 percent of the expected 40 hours of learning time per course credit. OUM learners also have the option of meeting in-class with a tutor and other students five times in a fifteen week semester. Increasingly, the self-managed and F2F components of the learning experience are being supported by online discussions and interactions with online digital learning objects. The chapter is summed up with ten major challenges currently faced by the OUM including issues such as sustainability, pedagogical effectiveness, efficiency, and the democratization of education.